Babel unbound : rage, reason and rethinking public life - Cowling, Lesley; Hamilton, Carolyn (Wits University Press, 2020)
In this timely and erudite collection, writers from the Global South demonstrate that forms of publicness are multiple, mobile and varied. Drawing primarily on materials from Africa for their capacity to speak to global developments, they propose new concepts and methodologies to analyse how public engagements work in society.